2020
DOI: 10.1017/jfm.2020.814
|View full text |Cite
|
Sign up to set email alerts
|

Influence of insoluble surfactants on shear flow over a surface in Cassie state at large Péclet numbers

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
0
18
1
Order By: Relevance
“…In the present study, we have assumed a flat liquid/air interface at the SH walls, following the recent works in the relevant literature (Yu, Teo & Khoo 2016;Crowdy 2017a;Hodes et al 2017;Patlazhan & Vagner 2017;Arenas et al 2019;Fairhall, Abderrahaman-Elena & García-Mayoral 2019;Schnitzer & Yariv 2019;Vagner & Patlazhan 2019;Landel et al 2020;Nayak et al 2020;Baier & Hardt 2021;Tomlinson & Papageorgiou 2022). This simplifying assumption has enabled us to tackle the problem of a viscoplastic fluid flow over the groovy SH wall, while addressing the complexities arising due to the yield stress effects, in a systematic way.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we have assumed a flat liquid/air interface at the SH walls, following the recent works in the relevant literature (Yu, Teo & Khoo 2016;Crowdy 2017a;Hodes et al 2017;Patlazhan & Vagner 2017;Arenas et al 2019;Fairhall, Abderrahaman-Elena & García-Mayoral 2019;Schnitzer & Yariv 2019;Vagner & Patlazhan 2019;Landel et al 2020;Nayak et al 2020;Baier & Hardt 2021;Tomlinson & Papageorgiou 2022). This simplifying assumption has enabled us to tackle the problem of a viscoplastic fluid flow over the groovy SH wall, while addressing the complexities arising due to the yield stress effects, in a systematic way.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…2020; Nayak et al. 2020; Baier & Hardt 2021; Tomlinson & Papageorgiou 2022). This simplifying assumption has enabled us to tackle the problem of a viscoplastic fluid flow over the groovy SH wall, while addressing the complexities arising due to the yield stress effects, in a systematic way.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…Recently, independent experimental studies have reported time-dependent and nonlinear dynamics that unequivocally demonstrate the importance of surfactant-induced stresses on SHSs [13][14][15]. Theoretical and computational works have then confirmed the extent to which trace amounts of these surfactant contaminants can influence liquid slip [15][16][17]. Indeed, ambient levels of surfactants, often extremely difficult to avoid or control in common experimental settings, are known to play a central role altering the behavior of numerous smallscale multiphase flows [18].…”
mentioning
confidence: 99%
“…The concentration gradients that induce interfacial Marangoni stresses appear in the streamwise direction, owing to stagnation points at the downstream ends of the interfaces where surfactants advected by the flow can accumulate. Initial theoretical studies only considered two-dimensional flows over transverse SHS gratings, since this is the simplest geometry to capture the negative effect of streamwise surfactant-induced Marangoni stresses [16,17]. However, these models cannot capture any three-dimensional effect.…”
mentioning
confidence: 99%
“…Understanding how surfactants equilibrate near contact lines is also important for flows over superhydrophobic surfaces, and slippery-liquid-infused porous surfaces (Wang & Guo 2020). As recently shown, surfactants can significantly affect the drag-reducing properties of superhydrophobic surfaces when a flow concentrates them at stationary contact lines (Landel et al 2020;Baier & Hardt 2021;Peaudecerf et al 2017). Surfactants are amphiphilic materials that accumulate at interfaces, where they lower surface tension.…”
Section: Introductionmentioning
confidence: 99%